Ternary Weighted Function and Beurling Ternary Banach Algebra l1ω(S) - Mehdi Dehghanian; Mohammad Sadegh Modarres Mosadegh (Abstract and Applied Analysis)
Let S be a ternary semigroup. In this paper, we introduce our notation and prove some elementary properties of a ternary weight function ω on S. Also, we make ternary weighted algebra l1ω(S) and show that l1ω(S) is a ternary Banach algebra.